Economic Evaluation of Participatory Social Forestry Management in Dhaka and Tangail Forest Divisions in Bangladesh - Safa, Mohamad Samaun (2004)
Sal (Shorea robusta) forests in Bangladesh comprise an area of 120,255 ha and are economically and environmentally important. Overexploitation has resulted in unsustainable use of timber and other non-timber forest products (NTFPs). The participatory social forestry management approach has been implemented by the Forest Department in order to protect the forests from encroachment and illegal exploitation. The study was conducted in Dhaka and Tangail Forest Division, Bangladesh to examine the effectiveness of the participatory social forestry management. The specific objectives were: (i) to examine the financial and economic viability of agroforestry (AF) and woodlot (WL) program, (ii) to determine the distribution impact of both programs, and (iii) to estimate the poverty reduction impact of both programs. The "with and without" approach was used in the study to estimate the net incremental benefit of the programs. Data required were obtained from primary and secondary sources. The respondents were the farmers. The sample size of the study was 375 comprise of the AF (118) and WL farmers (156). The cash-flow analysis approach was employed to determine the financial and economic viability of the participatory social forestry program. As an extension of cash flow analysis, the distribution impact and poverty reduction impact analyses were also carried out to examine the welfare perspective of the programs. The results showed that the respondents were of the middle age class (mean: 47 years old). The income from timber varies significantly between agroforestry and woodlot program. The majority of the respondents had primary level of education and agricultural labour was their main occupation. The results of the financial analysis showed that agroforestry program was feasible at 7 percent real discount rate. The financial net present value, benefit-cost ratio and financial internal rate of return were Tk. 20148.23, 1.32 and 15 percent, respectively. However, the WL was not feasible at 7 percent real discount rate. Both programs were found to be economically feasible with a different level of EIRR. The agroforestry program was PEB~STRKBAP~ SULTAN kw.k wtiR6F13 WTM WYW more feasible than the WL. The Economic Net Present Value, Benefit-cost Ratio and Economic Internal Rate of Return were Tk. 492687.06,3.08 and 67 percent, respectively, for the agroforestry program. The Economic Net Present Value, Benefit-cost Ratio and Economic Internal Rate of Return were Tk. 285560.55, 2.55 and 41 percent respectively for the woodlot program. Financial sensitivity analysis of the AF indicated that the fluctuation in the values of the key variables namely, rotation period, establishment cost, price of intercrop did not affect the project decision. The economic sensitivity analysis showed that the variations in values of key variables, namely protection cost, benefits of by product did not affect project decisions substantially. The results of distribution analysis showed that the benefit gained by the participants was greater than that of the government. The Poverty Impact Ratio was estimated at 0.95 for agro forestry program and 0.96 was for woodlot program. These values revealed that the impact of participatory social forestry management has been efficient in reducing the poverty level of the participants. Further research should focus on transaction costs and environmental aspects of the participatory social forestry management to encourage its extension.